Muscle fatigue and exercise-related biomarkers in amyotrophic lateral sclerosis - Francesca Bianchi; Lucrezia Becattini; Lucia Chico; Giulia Ricci; Gabriele Siciliano (Exploration of Neuroprotective Therapy, 2023)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disorder affecting motor neurons. The complex etiopathogenetic mechanism of ALS can lead to extensive alterations, including cortical changes, neuroinflammation, and changes in muscular structure. These ALS-derived alterations may contribute to fatigue, a symptom severely impacting patients’ quality of life that is commonly associated with muscular exercise. Intriguingly, muscular exercise can be at once a promoter of motor neuron degeneration in predisposed patients as well as an effective non-pharmacological treatment of ALS. To fully disclose its therapeutic potential, muscular exercise must be tailored to patients’ phenotypes, balancing potential benefits and risks that are unique to each ALS case. Biomarkers of muscular fatigue, with their potential for insight into inflammation and oxidation, can be used to ensure that the intensity of physical activity remains below the threshold level beyond which exercise might become harmful. In this review, the authors explore the concept of fatigue in ALS patients, focusing on fatigue generation, definition, detection, quantification, and treatment. The study discusses the most important fatigue biomarkers, putting them in relation to the mechanism of fatigue generation and with monitoring of muscular exercise as a possible treatment of fatigue.